2019
DOI: 10.1002/jcb.29479
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of infiltrating immune cells in clear cell renal cell carcinoma (ccRCC)

Abstract: In this study, we attempted to evaluate the prognostic value of infiltrating immune/stromal cells in clear cell renal cell carcinoma (ccRCC), by using the immune scores and stromal scores based on the “Estimation of STromal and Immune cells in MAlignant Tumours using Expression data” algorithm to represent the levels of infiltrating immune cells and stromal cells. We found that the infiltrating immune cells were associated with poor prognosis of ccRCC. To assess the role of infiltrating immune cells in ccRCC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
(64 reference statements)
2
12
0
Order By: Relevance
“…Taken together, the above analysis and experimental results suggested that ACE2 was low expressed in ccRCC, and higher ACE2 expression was related to better prognosis and pathological features of ccRCC patients. [26]. A recent study through the analysis of various databases indicates that ACE2 expression in Uterine Corpus Endometrial Carcinoma and Kidney Renal Papillary Cell Carcinoma was significantly increased, which was positively correlated with immune infiltration and prognosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the above analysis and experimental results suggested that ACE2 was low expressed in ccRCC, and higher ACE2 expression was related to better prognosis and pathological features of ccRCC patients. [26]. A recent study through the analysis of various databases indicates that ACE2 expression in Uterine Corpus Endometrial Carcinoma and Kidney Renal Papillary Cell Carcinoma was significantly increased, which was positively correlated with immune infiltration and prognosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Two preceding studies also support our findings and revealed that immune scores calculated by ESTIMATE were associated with poor survival. [ 7 , 9 ] Generally speaking, activated immune T cells are related to a good prognosis of ccRCC. [ 30 ] However, B cells increase in late-stage RCC and can reduce the proportion of T cells in cancer microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] It has been reported that immune cells and stromal cells in the tumor microenvironment play a crucial role in regulating the biological processes of cancer cells. [ 7 ] Previous research has shown that immune scores calculated by gene expression data can be used to infer the infiltration of immune cells and stromal cells in cancer tissues. [ 8 ] In addition, several studies also reported that immune infiltration is correlated with the prognosis of patients with ccRCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESTIMATE algorithm has been employed in glioblastoma, [ 20 ] bladder cancer, [ 21 ] and renal clear cell carcinoma. [ 22 ]…”
Section: Introductionmentioning
confidence: 99%